1997
DOI: 10.1177/146642409711700307
|View full text |Cite
|
Sign up to set email alerts
|

Non-group A streptococci: are they pathogens in the throat?

Abstract: A total of 3,184 paediatric patients with sporadic pharyngitis was studied at King Khalid University Hospital in Riyadh, Saudi Arabia. In addition, 478 children without pharyngitis who were matched for age and sex were included as controls. Group A beta-haemolytic streptococci (beta HS) were detected significantly more often among the children with pharyngitis than among the controls (8.4% vs 2.3%; p < 0.0001). In contrast, total non-group A and group C beta HS were isolated at lower frequency from the sick th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
6
0
4
Order By: Relevance
“…dysgalactiae subsp. equisimilis appartiene al gruppo C o G di Lancefield ed è responsabile di rare epidemie di faringotonsillite nelle popolazioni adulta e pediatrica (1); è invece considerato un agente eziologico inusuale di episodi tonsillitici acuti a carattere sporadico (2). Sono documentati tra l'altro episodi di setticemia, endocardite, polmonite, meningite, sostenuti da S. dysgalactiae subsp.…”
Section: Introduzioneunclassified
See 2 more Smart Citations
“…dysgalactiae subsp. equisimilis appartiene al gruppo C o G di Lancefield ed è responsabile di rare epidemie di faringotonsillite nelle popolazioni adulta e pediatrica (1); è invece considerato un agente eziologico inusuale di episodi tonsillitici acuti a carattere sporadico (2). Sono documentati tra l'altro episodi di setticemia, endocardite, polmonite, meningite, sostenuti da S. dysgalactiae subsp.…”
Section: Introduzioneunclassified
“…Sono documentati tra l'altro episodi di setticemia, endocardite, polmonite, meningite, sostenuti da S. dysgalactiae subsp. equisimilis, che non è pertanto agente eziologico di sole infezioni dell'alto tratto respiratorio (1,2). Le infezioni faringotonsillari da streptococchi dei gruppi C e G di Lancefield sono talora responsabili di incremento del titolo antistreptolisinico e dello sviluppo di sequele non suppurative, in particolare glomerulonefrite ed artrite reattiva (6,7), similmente a quanto ormai noto a proposito delle infezioni da S. pyogenes.…”
Section: Introduzioneunclassified
See 1 more Smart Citation
“…Although there have been numerous reports of epidemic group C and G streptococcal pharyngitis in adults [8±13], their signi®cance as a cause of pharyngitis in children is less ®rmly established. Chowdhury et al [14] considered them not to be signi®cant, whereas Cimolai et al [15] found large colony isolates to be signi®cant when isolated in moderate to large numbers from a throat culture, and Martin et al [12] demonstrated that group G streptococci of one DNA ®ngerprint pattern were isolated from 73% of cases during a paediatric outbreak of streptococcal pharyngitis.…”
mentioning
confidence: 99%
“…Studies have reported conflicting incidence rates of non-GAS in symptomatic versus asymptomatic individuals. [3][4][5] One study of children found that group C streptococcus can cause exudates, sore throat, and fever, 6 although whether these children respond to antibiotics remains controversial. 7 Although group C pharyngitis is common in adults, only one study found rates of fever, exudates, and cervical adenopathy similar to those rates found in individuals with GAS pharyngitis.…”
mentioning
confidence: 99%